Hazardous Materials Medicine Treating the Chemically Injured Patient - Stilp, Richard H.; Bevelacqua, Armando S. (Wiley, 2023)
Hazardous Materials Medicine Complete background on chemical exposures that create illnesses, including assessment, diagnosis, and treatment protocols. Written on a level that can be understood by field practitioners and/or first responders, Hazardous Materials Medicine: Treating the Chemically Injured Patient provides an in-depth understanding of how to diagnose and treat toxic chemical exposures in a prehospital or emergency department setting. The protocols used in this book conform to the guidelines set forth in the NFPA 470 standard, and the medical guidance developed by FEMA for Type I, II & III Deployable Hazmat Response Teams. The hazardous materials medical protocols in this book have been fully vetted by three poison control toxicologists, multiple emergency physicians, and paramedics. Enabling public safety and health professionals to administer effective care while retaining their own personal safety, Hazardous Materials Medicine: Treating the Chemically Injured Patient is a must-have resource for emergency medical technicians, paramedics, hazmat technicians, and emergency physicians and nurses working in high-risk field situations with chemically injured patients.